KERJASAMA INDONESIA DENGAN UNICEF MELALUI PROGRAM ROOTS UNTUK MENANGANI KASUS PERUNDUNGAN ANAK TAHUN 2017-2018 - RIFQHI FAUZAN (2020)
Bullying, especially in the school environment, is a serious problem, but it is not being addressed. Almost every country has reports of acts of bullying, including Indonesia. Indonesia is a country that requires its people to have 12 years of education, which should make the education environment a safe and comfortable environment for students. However, there are still many cases of bullying that occur in schools, both intentional and unintentional. This case received attention from UNICEF. UNICEF finally decided to cooperate with the Government of Indonesia in dealing with this case. The cooperation is carried out through the extension of the Government of Indonesia through the relevant Dinas parties, institutions that fight for the rights of children, and other parties. This collaboration then resulted in the ROOTS program, a program to prevent and handle cases of bullying in Indonesia. This research uses a qualitative approach, descriptive research type, the source used is secondary data obtained from the official website of the institution concerned with the issue under study, namely UNICEF, and through literature study. The data obtained were analyzed using the theory of international cooperation. Based on the data analysis conducted, it can be concluded that the collaboration between UNICEF and the Government of Indonesia through the ROOTS program was declared successful in overcoming cases of bullying in Indonesia. Keywords: UNICEF, Indonesian Government, Child Abuse, ROOTS